(untitled) (Nepal Journal of Epidemiology, 2013)
"Some scientists "published research article" will be having lots of "citations" but it might not be published in a "high impact factor journal". There is no value for these scientists? DOI: http://dx.doi.org/10.3126/nje.v3i4.9497